Real time internet instrumentation / Zuhaina Zakaria and Bibi Norasiqin Sheikh Rahimullah - Zakaria, Zuhaina; Sheikh Rahimullah, Bibi Norashiqin (2001)
This research project describes the software development of remote access and control for realtime measurement via the Internet. The philosophy behind this remote laboratory is based on a client/server computer configuration. The client is a computer equipped with user interface functions, which gives users the ability to act on the remote experiment. On the other hand, the server is the computer located near the real process and equipped with the hardware interface to the experiment. The server software receives the client commands and transmits them to the real process. The advancement of Internet technology enables them to communicate, transferring both data and command at real time. A simple test circuit was designed for the purpose of measurement. Microsoft Visual Basic was then used to develop the graphical user interface (GUI). This GUI enables users to manipulate the data received according to their needs.